Peran Sistem Informasi Manajemen Dalam Mewujudkan E-Government - Annisa Sagala; Rayyan Firdaus (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
Management Information Systems (MIS) have an important role in the transformation of government towards E-Government. E-Government is a government effort to provide public services electronically to the public and businesses. In this context, SIM plays a role as the main support in managing information and making effective and efficient decisions. The role of Management Information Systems (MIS) in realizing E-Government is very important in increasing the efficiency and effectiveness of public services. SIM helps governments manage information, plan strategies, coordinate activities, and make better decisions. Through SIM, the government can increase information accessibility for the public, speed up the decision-making process, and improve the overall quality of public services. Thus, effective and efficient implementation of SIM will make a major contribution to realizing an E-Government that is transparent, accountable and responsive to community needs.